1980
DOI: 10.1002/jmv.1890060203
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis b virus, hepatitis a virus and persistently elevated aminotransferases in hemophiliacs

Abstract: To determine the exposure to hepatitis A and hepatitis B viruses (HAV, HBV) following intravenous replacement therapy in patients with classic hemophilia and to assess the role of these viruses in persistently elevated aminotransferases, sera were studied from 136 patients from 9 months to 67 years of age were transfused with either single-donor cryoprecipitate (CRYO) or Antihemophilic Factor Concentrate (AHF) for periods ranging from a few months to 15 years. Serologic evidence of past or present infection wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…However, regarding 2 patients who had been given clotting factors in addition to blood transfusions, these blood derivatives have to be considered possible sources of infection. Such preparations that are pro duced from large plasma pools do indeed bear a considerable risk of infection, despite screening of donors for HBsAg [14,23,30,34], With respect to the remaining 5 patients, especially in consideration of the compre hensive investigations of our study, there is no reason whatsoever to assume causal con nection between blood transfusion and hep atitis that was reported subsequently. There fore, in these cases, it is not correct to use the term 'posttransfusion hepatitis' that implies transfused blood to be the source of infec tion.…”
Section: Discussionmentioning
confidence: 55%
“…However, regarding 2 patients who had been given clotting factors in addition to blood transfusions, these blood derivatives have to be considered possible sources of infection. Such preparations that are pro duced from large plasma pools do indeed bear a considerable risk of infection, despite screening of donors for HBsAg [14,23,30,34], With respect to the remaining 5 patients, especially in consideration of the compre hensive investigations of our study, there is no reason whatsoever to assume causal con nection between blood transfusion and hep atitis that was reported subsequently. There fore, in these cases, it is not correct to use the term 'posttransfusion hepatitis' that implies transfused blood to be the source of infec tion.…”
Section: Discussionmentioning
confidence: 55%
“…Most recipients of non-heat-treated plasma-derived factor concentrates have been infected with HBV [50] and HCV [40,51]. At least 50% of those infected with HCV get chronic hepatitis, and many eventually get cirrhosis [52].…”
Section: Impact Of Hepatitismentioning
confidence: 99%
“…143]. Due to their high usage of blood products, hemophiliacs are especially at risk, and 90% have serological evidence of exposure to hep atitis B virus [144], In a study of 1,332 hemo philiacs [145], 72% showed at least one ab normal value for AST over a 6-month peri od, and 16-20% lacking evidence of hepatitis B virus infection had persistently elevated levels. Because of the limited supply of donor blood.…”
Section: Screening For Hepatitis Non-a Non-b (Nanb)mentioning
confidence: 99%